Предмет: Алгебра,
автор: Аноним
6(3-х)=2х+8 Помогите решить
Ответы
Автор ответа:
0
6(3-х)=2х+8
18-6х=2х+8
-6х-2х=8-18
-8х=-10 (обе части уравнения умножаем на -1)
8х=10
х= 10:8=1,25 или в виде обыкновенной дроби
18-6х=2х+8
-6х-2х=8-18
-8х=-10 (обе части уравнения умножаем на -1)
8х=10
х= 10:8=1,25 или в виде обыкновенной дроби
Похожие вопросы
Предмет: Математика,
автор: gggguuuu4d
Предмет: Математика,
автор: 1234frog59
Предмет: Математика,
автор: Jazzu
Предмет: Математика,
автор: 22842
Предмет: Алгебра,
автор: makssapronov